Restorative Justice, Consistency and Proportionality: Examining the Trade-off. Issue 2 (4th May 2019) - Tiarks, Elizabeth
Abstract: Restorative justice conferences that operate as sentencing mechanisms involve the making of a trade-off between empowering lay participants to make their own decisions, and the requirements of consistency and proportionality, which are established principles of sentencing. In current restorative justice practice, this trade-off tends to be made more in favour of consistency and proportionality, at the expense of the empowerment of lay participants. Empowerment is central to key benefits of restorative justice, such as reducing recidivism and increasing victim satisfaction. However, its importance to the effectiveness of restorative justice is not always properly acknowledged. In addition to this lack of acknowledgment, there are both conceptual and practical problems with the principles of consistency and proportionality (particularly in the way that they are presented when considered in relation to restorative justice) that are often overlooked. As a result, the tendency is for assumptions to be made about the necessary supremacy of these principles over empowerment. This paper urges more acknowledgement of the importance of empowerment in restorative justice, together with a greater appreciation of the problems with consistency and proportionality, with a view to challenging assumptions about the way that the trade-off must be made.